CERAI GUGAT (KHULU’) KARENA SUAMI HILANG (MAFQUD) PERSPEKTIF FIKIH HAMBALI (Analisis Putusan Pengadilan Agama Sorong Nomor 57/Pdt.G/2018/PA.Srog) - Jundulloh, Abdurrohman Muhammad; Ahsan, Khoirul (AS-SALAM, 2024)
Abstract Mafqud, according to the Hambali madzhab, is someone who has disappeared from his place of residence and his whereabouts and news are unknown, whether he is alive or dead. Mafqud is one of the reasons for the permissibility of divorce (khulu') or faskh. The purpose of this study is to provide an understanding of the Hambali fiqh perspective on this issue and slightly analyze whether the court's decision is in accordance with the Hambali fiqh perspective. This research uses literature review. The method used is qualitative analysis. The results of this study are: In the case of mafqud who is dhamically safe, the wife must wait up to 90 years from the birth of the person. Meanwhile, if the mafqud who is not physically safe, then after the lapse of 4 years from the disappearance of the husband is considered dead. After that, the wife can have an iddah period of four months and ten days. The decision of the Sorong Religious Court Number 57/Pdt.G/2018/PA.Srog in this discussion according to the author is in accordance with the perspective of Hambali fiqh. Keywords: Divorce, Mafqud, Hambali Fiqh. Abstrak Tujuan dari studi ini adalah untuk memberikan pemahaman tentang perspektif fikih Hambali dalam masalah ini dan sedikit menganalisis apakah putusan pengadilan tersebut sudah sesuai dengan perspektif fikih Hambali. Mafqud, menurut madzhab Hambali adalah seseorang yang hilang dari tempat tinggalnya dan tidak diketahui keberadaan serta kabarnya apakah masih hidup atau sudah mati. Mafqud merupakan salah satu alasan diperbolehkannya cerai gugat (khulu’) ataupun faskh. Penelitian ini menggunakan kajian studi pustaka. Metode yang digunakan adalah analisis kualitatif. Hasil dari penelitian ini adalah: Apabila mafqud yang secara dzahirnya selamat, maka istri harus menunggu hingga 90 tahun sejak kelahiran orang tersebut. Sedangkan jika mafqud yang secara dzahirnya tidak selamat, maka setelah lewat 4 tahun dari hilangnya suami dianggap sudah mati. Setelah itu, istri bisa bermasa iddah selama empat bulan sepuluh hari. Adapun putusan Pengadilan Agama Sorong Nomor 57/Pdt.G/2018/PA.Srog dalam pembahasan ini menurut penulis sudah sesuai dengan perspektif fikih Hambali. Kata Kunci: Cerai Gugat, Mafqud, Fikih Hambali.